Effect of Linear Alkylbenzene Sulfonate on Mortality, Hatching Rate of Eggs and Abnormality of Catfish (Pangasius hypophthalmus Sauvage) Larvae - Supriyono, E.; Lisnawati, L.; Djokosetiyanto, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
Linear alkylbenzene sulfonate (LAS) surfactant in the water can affecting fish in all developmental stages. This study was aimed to observe the effect of LAS on mortality, hatching rate of eggs, and abnormality of patin catfish (Pangasius hypophthalmus Sauvage) larvae. Fertilized eggs were incubated in water containing LAS at the dosages of 0.0, 0.5, 1.5, 3.0, 9.0, and 18.0 mg/L. Eggs mortality was observed every 6 hours until larvae hatched (24 hours). The results of study showed that the exposure of 18.0 mg LAS per liter water could put to death all the fertilized eggs and larvae be abnormal. The exposure of LAS at concentration of 9.0 mg/L could kill 98% of eggs and hatching rate was only 2%. The abnormality in larvae was bending in the body and tails. Keywords: patin catfish, Pangasius, Linear Alkylbenzene Sulfonate, LAS, abnormality ABSTRAK Surfaktan Linear Alkylbenzene Sulfonate (LAS) yang masuk ke dalam perairan sangat berpengaruh terhadap ikan dari stadia awal hidup ikan sampai dewasa. Penelitian ini bertujuan untuk mengetahui pengaruh LAS terhadap mortalitas, daya tetas telur dan abnormalitas larva ikan patin (Pangasius hypophthalmus Sauvage). Telur ikan patin yang telah dibuahi di rendam dalam air yang mengandung LAS dengan konsentrasi 0,0; 0,5; 1,5; 3,0; 9,0 dan 18,0 mg/L. Mortalitas telur dicatat setiap 6 jam sampai menetas (24 jam). Hasil penelitian menunjukkan bahwa konsentrasi LAS sebesar 18,0 mg/L dapat mengakibatkan mortalitas telur dan abnormalitas pada larva secara total. Konsentrasi LAS sebesar 9,0 mg/L dapat mematikan telur hingga 98% dan hanya menghasilkan daya tetas sebanyak 2%. Abnormalitas pada larva berupa pembengkokan pada tubuh dan ekor. Kata kunci: ikan patin, Pangasius, Linear Alkylbenzene Sulfonate, LAS dan abnormalitas